Growth Hormone Impact and Insights in Human Beings - Bernardo-Filho, Mario; da Cunha de Sá-Caputo, Danubia; Maria de Oliveira Maranhão, Tecia; Taiar, Redha (IntechOpen, 2023)
Growth Hormone - Impact and Insights in Human Beings presents aspects of the importance of growth hormone and the complexity of its actions, from biochemistry to its relevance to the growth of an individual. The gene family that generates isoforms of the GH, as well as the pituitary growth hormone secretion and signaling pathways, are discussed. Interventions to prevent disease or increase the serum concentration of growth hormone, such as physical exercises, are also explored. This information aims to contribute to understanding the management of clinical conditions involving the growth hormone and to support readers in decision-making.